Diseño de la relavera en la planta de Beneficio de Minerales “Alto Vizcaya” Código 390356, cantón Zaruma, provincia de El Oro - Mendieta Cueva, Doménica Salomé (2025)
Tailings are waste from mineral processing, in the case of the “Alto Vizcaya” Plant code 390356 it consists of the stages of comminution (crushing – grinding), subsequent cyanidation with activated carbon. Materials that have no economic value are taken to a thickening tank where flocculant is added to increase their density and obtain lower moisture content, then they are transported to the tailings dam for final disposal. The tailings dam must have the capacity to store the volume of tailings generated according to the operational capacity of the plant, which is why this work focuses on the design for the thickened tailings deposit. The first step is to determine the characteristics of the area such as geology, geomorphology, topography, and hydrology, thereby determining the location where soil analyses were performed, including SPT and refraction seismic, which served to perform the stability analysis. The second point is the characteristics of the tailings, which are used to determine the amount of volume to be deposited and its conditions. In this way, a pH of 8, equivalent to alkaline, density of 1.48 Ton/m3, percentage of solids of 76.96%, and finally the granulometry, in which 59% passes sieve 150, was determined. Regarding mineralogy, the tailings are composed of silica, potassium, iron and aluminum oxides, sulfides such as pyrite, and elements such as magnesium and copper. For the design of the tailings dam, the central axis arrangement method was determined, which consists of locating the dam containing the tailings dam basin to place the tailings in an ascending manner. Additionally, rock was considered as borrow material for the construction of the dam. Likewise, the implementation of a crown ditch for drainage resulting from the collection of rainwater and water obtained from the sedimentation process of the tailings was considered. Finally, the stability analysis was carried out using the simplified Bishop method, thus the analysis was carried out under normal conditions (static) and under earthquake conditions (pseudostatic), in which a safety factor of 1.5 was obtained for the first and 1.1 for the second, these values are established within the Ecuadorian Construction Standard, which guarantee the stability of the structure.